PENGARUH REPUTASI, BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN STUDI PADA PENGGUNA KOSMETIK WARDAH DI KOTA PALEMBANG: PENGARUH REPUTASI, BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN STUDI PADA PENGGUNA KOSMETIK WARDAH DI KOTA PALEMBANG - cia, HelisiaKrisdayanti (Asyafina Journal: Jurnal Akademi Pesantren, 2024)
This research aims to determine the influence of reputation and Brand Image on Purchase Decisions for a study of Wardah Cosmetics Users in Palembang City, in this study namely knowledge of reputation (X1), and Brand Image (X2), while the dependent variable in this study is purchasing decisions (Y ). The population in this study were all customers of Bank Sumsel Babel Syariah Palembang Branch Office. The sample was 100 customers using the Lemeshow formula and using incidental sampling techniques. The data used is primary data. The data analysis technique in this research uses SPSS, which consists of classic assumption tests, multiple linear regression tests, and hypothesis tests. The results of this research were obtained from the t test and F test which showed that the reputation variable, brand image had a positive and significant effect on purchasing decisions partially and simultaneously.